The Contamination of Heavy Metals in Water and Sediments from Balekhiley Community Fishing Narathiwat Province - Adam, Rohana (Princess of Naradhiwas University Journal, 2019)
This research isstudying the quality of water and the quantity of heavy metals such as zinc (Zn), cadmium (Cd), copper (Cu), lead (Pb) and nickel (Ni)in the water sample and sediments.The sample were collected 12 stations by Atomic Absorption Spectrometer duringMarch 2016 and November 2016 from Balekhiley community fishing Narathiwas Province. The quality of water and concentration of zinc (Zn), cadmium (Cd), copper (Cu), lead (Pb) and nickel (Ni) were found in range of0.112–0.298, 0.001–0.016, 0.006–0.021, 0.001–0.019 and 0.001–0.018 mg/l, respectively.The concentration of quality of waterand heavy metals werelower than the permitted value ofsurface water quality standard bythe Pollution Control Department.The sediments samples analysis were found thatthe zinc (Zn), cadmium (Cd), copper (Cu),lead (Pb) and nickel (Ni) concentration detected in range of 20.25–49.10, 0.10–0.41, 10.08–29.58, 2.01–14.99 and 1.10–7.89 mg/kg, respectively. The concentration of heavy metals were found that they were lower than the permitted standard value of sediment quality by the Pollution Control Department and NOAA. The highest value of heavy metal were zinc (Zn), copper (Cu), lead (Pb), nickel (Ni) and cadmium (Cd), respectively.